Non-invasive intraventricular pressure differences estimated with cardiac MRI in subjects without heart failure and with heart failure with reduced and preserved ejection fraction. Issue 2 (9th October 2019) - Londono-Hoyos, Francisco; Segers, Patrick; Hashmath, Zeba; Oldland, Garrett; Koppula, Maheshwara Reddy; Javaid, Khuzaima; Miller, Rachana; Bhuva, Rushikkumar; Vasim, Izzah; Tariq, Ali; Witschey, Walter; Akers, Scott; et al.
Abstract : Objective: Non-invasive assessment of left ventricular (LV) diastolic and systolic function is important to better understand physiological abnormalities in heart failure (HF). The spatiotemporal pattern of LV blood flow velocities during systole and diastole can be used to estimate intraventricular pressure differences (IVPDs). We aimed to demonstrate the feasibility of an MRI-based method to calculate systolic and diastolic IVPDs in subjects without heart failure (No-HF), and with HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). Methods: We studied 159 subjects without HF, 47 subjects with HFrEF and 32 subjects with HFpEF. Diastolic and systolic intraventricular flow was measured using two-dimensional in-plane phase-contrast MRI. The Euler equation was solved to compute IVPDs in diastole (mitral base to apex) and systole (apex to LV outflow tract). Results: Subjects with HFpEF demonstrated a higher magnitude of the early diastolic reversal of IVPDs (−1.30 mm Hg) compared with the No-HF group (−0.78 mm Hg) and the HFrEF group (−0.75 mm Hg; analysis of variance p=0.01). These differences persisted after adjustment for clinical variables, Doppler-echocardiographic parameters of diastolic filling and measures of LV structure (No-HF=−0.72; HFrEF=−0.87; HFpEF=−1.52 mm Hg; p=0.006). No significant differences in systolic IVPDs were found in adjusted models. IVPD parameters demonstrated only weak correlations with standard Doppler-echocardiographic parameters. Conclusions: Our findings suggest distinct patterns of systolic and diastolic IVPDs in HFpEF and HFrEF, implying differences in the nature of diastolic dysfunction between the HF subtypes.